Product Innovation Development Strategy to Increase Company Competitiveness at PT. Shavira Barokah Utama (Camille Beauty) - Adawiyah, Nurul; Pasaribu, Veta Lidya Delimah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to uncover the new product development strategies implemented by PT. Shavira Barokah Utama (Camille Beauty) in the cosmetics industry. Through a qualitative approach, this study analyzes how the company has successfully maintained its competitiveness through innovations in formula, packaging, and marketing. The findings indicate that Camille Beauty consistently introduces products that meet the evolving needs of consumers. This research is expected to contribute to a deeper understanding of innovation strategies in the beauty industry and provide recommendations for other businesses.